(untitled) (Experimental biology, 2021)
Based on the high nutritional and biological value of mare’s milk, the uniqueness of its protein, fat, vitamin and mineral compositions, the article provides information on the chemical composition of dry mare’s milk obtained by freeze-drying. On the basis of dry mare’s milk, a recipe for sports nutrition has been developed, including additional raw materials that increase not only the biological value of the product, but also give it targeted medico-biological properties. antioxidants, polysaccharide-fucoidan, dry wheat germ, dry cream). The product had a high nutritional and biological value and good organoleptic characteristics. On a swimming model, the effectiveness of the product was assessed on Wistar rats, who received 10 g of a specialized product in addition to the main semi-synthetic diet daily for 35 days. The consumption of a specialized sports nutrition product by animals for 35 days increased the endurance and performance of rats when swimming with a load. Compared with the initial data, the swimming time of the animals in the experimental group increased 3.0 times, while the swimming time in the control group exceeded the initial values only 1.5 times. After a 35-day intake of the product against the background of a swimming load, a positive dynamics was noted in the change in the parameters of the LPO-AOD system – a decrease in the level of malondialdehyde and diene conjugates in the membranes of erythrocytes by 35.0 and 41.4%, respectively, compared with control animals. A similar relationship was found for the mitochondrial fraction of skeletal muscles. The obtained changes indicate a favorable effect of the product on endurance, performance and the state of the antioxidant defense system, as well as the energy metabolism of laboratory animals. Key words: mare’s milk, sports nutrition, swimming, antioxidant status. Key words: mare’s milk, sports nutrition, swimming, antioxidant status.